ANALYSIS OF THE APPLICATION OF FISCAL CORRECTIONS TO COMMERCIAL FINANCIAL REPORTS TO DETERMINE THE CALCULATION OF TAX PAYABLE (Case Study of PT. XXZ) - Imelda Praktis Laia (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2024)
The purpose of this research was to determine the preparation of fiscal corrections that have been presented by the company, in accordance with tax provisions. Fiscal adjustments need to be made to determine the calculation of income tax, due to differences in revenue and cost recognition according to financial accounting standards and taxation provisions. The research was conducted using a descriptive statistical analysis method, which is to thoroughly describe the fiscal corrections carried out by the company, the data used are primary data, namely the data sources provided by the company in the form of financial statements and records used, and secondary data, namely the source of data obtained in the form of literature and literature studies related to this research. The results of this study indicate that the financial statements prepared by the company were not in accordance with tax provisions, that several fiscal correction errors were found and several transaction accounts that had not been corrected, resulting in differences in the amount of taxable income before and after analysis. From this fiscal correction, an underpayment of the company's payable tax is greater than the previous calculation, and the impact on the company may be subject to a late payment penalty from the remaining unpaid underpayment.